Pengukuran Kualitas E-Learning LMS Moodle dengan Metode PIECES Framework dan Equivalence Partitioning - Kadek Kusuma Dewi; Dwi Putra Githa; Ni Made Ika Marini Mandenni (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Technological Technological developments affect the process of improving various fields of community service, one of which is education. The form of improving the quality of services in the field of education is e-learning at SMAN 2 Tabanan. The use of LMS is relatively new and a review is needed so that it can be used both online and offline. The quality measurement of SMAN 2's LMS was carried out to see the results of the evaluation of the LMS system on the success rate of using e-learning in the teaching and learning process. Quality measurement is carried out using the PIECES Framework and Equivalence Partitioning methods. The PIECES Framework is a method with six variables and 19 indicators. Equivalence Partitioning is a system test using two outputs, namely valid and invalid. The results of the measurement of the PIECES variable are in the range of values from 3.09 with the Fair category to 3.88 with the indicator category achieving Good results. The results of the Equivalence Partitioning Technique test obtained an effectiveness of 100%, which means that the e-learning functionality has been running well. The Equivalence Partitioning test supports the results of the PIECES questionnaire for providing recommendations for indicators that score below 3.40